Caracterizaçao morfofuncional de praticantes do brazilian jiu-jitsu - Silva Bricio Rezende, Rafaela (2019)
Objective of this study was to characterize the morphofunctional profile of Brazilian Jiu-jitsu (BJJ) amateur athletes, making a comparison by gender. Participated, 19 practitioners of the modality (7 women: 21.29 ± 4.68 years of age, 25.84 ± 3.90 kg/m2 BMI, 22.03 ± 8.20% body fat and 12 men: 22 , 03 ± 6.04 years of age, 23.98 ± 4.08 kg/m2 of BMI, 14.53 ± 8.66% of body fat) for at least one year and with graduation level between white belt it's blue. These were submitted to assessments related to body composition and flexibility, manual grip strength and lower limb power. After the evaluations the comparison between the gender was performed through the Student t test to sample independent (p0.05). The only variables that presented significant differences were those related to manual grip strength (right - 47.35 ± 8.77N and 30.28 6.65N, left - 40.75 ± 8.45 N and 25.57 ± 5,94N) and height of the vertical jump (33.34 ± 4.98cm and 23.33 ± 4.30cm), being statistically superior for men. The other variables did not present significant differences. Concluded that men have higher levels of strength when compared to women.